Kapan Profesi Auditor Internal diminati? Pengujian Eksperimen terhadap Label Pekerjaan, Peran Auditor Internal dan Prospek Karir - Mayar Afriyenti; Vita Fitria Sari (Jurnal Dinamika Akuntansi dan Bisnis, 2018)
It is a big challenge for companies to recruit the best talent for the position of internal auditor. This challenge is increasing with the presence of various kinds of negative perceptions (stereotypes) regarding this profession. Using an experimental approach, this study examines the effect of job label, the primary role of internal auditors and career prospect toward the willingness of job applicants to apply the internal auditor position. Two experiments were conducted to answer the research questions with the design of each 1x2 and 2x2 between-subjects. The results of the study indicated that the willingness of job applicants was higher if the job was labeled with an accountant than labeled as internal auditor. These findings indicated that not only candidates with work experience were reluctant to apply for the position of internal auditors, but also from fresh graduates applicants. The applicant's willingness is higher if the primary role of internal audit department is more directed as a provider of consulting services than its conventional role as an assurance function. The applicant's willingness is higher when the accomplished staff will be promoted to a higher position outside the internal audit department than to be one of the leaders within the internal audit department. These findings suggest that organizations should design internal audit departments more precisely to support effective organization governance.